(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2023)
Pornography sites receive up to 75 million daily visits and digital technologies have made explicit sexual content more visible and accessible than ever before. Its intense consumption revived the interest of researchers in understanding what would justify the audience’s demand for pornography, as well as its possible effects, because, conceiving such relationships have direct consequences in the regulation and standardization of their production and circulation. In this sense, we seek to understand the motivations, the uses of the pornography by the audience, through a literature review that privileged the approach of the theoretical tradition of Uses and Gratifications. It also sought to expose our main findings: (i) manipulation of physiological reactions; (ii) social interaction; and (iii) self-awareness. In the end, we theoretically established the relationships between the uses and the possible effects of pornography on its users.